The epistles of Paul to the Colossians and Philemon an introduction and commentary - Wright, Nicholas Thomas, 1948- (Leicester, UK IVP, 1986)
Includes bibliographical references.
Keywords: Bible. N.T. Colossians -- commentaries; Bible. N.T. Philemon -- commentaries